P123 Opiate Smokers have a High Prevalence of Respiratory Symptoms Irrespective of Airflow Obstruction. (14th November 2013) - Lewis-Burke, N; Wooding, O; McKinnell, K; Davies, L; Walker, PP
Abstract : In the 1990s inhalation ('chasing the dragon') became the predominant method of recreational opiate (heroin and crack cocaine) consumption as it was perceived to have fewer detrimental health effects than injection. Although clinicians encounter individuals with COPD associated with opiate smoking ('heroin lung') the airway effects and symptoms resulting from opiate smoking are not established. We recruited 145 current and past opiate users from a local community drug service and recorded demographics. They completed spirometry pre and post salbutamol and questionnaires addressing drug use, symptoms and health status. Lower limit of normal was used to define airflow obstruction. Ten subjects failed to produce adequate spirometry, 26 had only injected and never smoked opiates while 6 subjects had marked bronchodilator (BD) reversibility consistent with asthma. Thirty six subjects appeared to have COPD and these were compared with 67 opiate smokers with normal post-BD spirometry and the 26 subjects who only injected opiates. The results from the 3 groups are shown in the table. The COPD group was a little older and necessarily had a lower FEV1 and post-BD airflow obstruction. There was little difference in length of drug use when the opiate smokers with COPD were compared to those without and the frequency of cough and phlegm differed little. Opiate smokers with COPD had modestly higher rates of wheeze and breathlessness; hence, higher CAT and MRC dyspnoea scores, but respiratory symptoms and use of respiratory medication were common in the non-COPD groups. Heroin and crack cocaine smoking is a risk factor for the development of irreversible airflow obstruction at a very young age. Respiratory symptoms are common in opiate smokers irrespective of the presence of COPD and not uncommon in those who have only injected opiates. In many, this is associated with a reduced health status despite normal spirometry; hence, symptoms are not a useful way to 'diagnose' COPD and spirometry is essential.